The Limits of Natural Selection in a Nonequilibrium World - Brandvain, Yaniv; Wright, Stephen I. (Trends in genetics, 2016)
Evolutionary theory predicts that factors such as a small population size or low recombination rate can limit the action of natural selection. The emerging field of comparative population genomics offers an opportunity to evaluate these hypotheses. However, classical theoretical predictions assume that populations are at demographic equilibrium. This assumption is likely to be violated in the very populations researchers use to evaluate selection's limits: populations that have experienced a recent shift in population size and/or effective recombination rates. Here we highlight theory and data analyses concerning limitations on the action of natural selection in nonequilibrial populations and argue that substantial care is needed to appropriately test whether species and populations show meaningful differences in selection efficacy. A move toward model-based inferences that explicitly incorporate nonequilibrium dynamics provides a promising approach to more accurately contrast selection efficacy across populations and interpret its significance. Next-generation DNA and RNA sequencing datasets are enabling powerful genomic tests of the factors influencing the efficacy of natural selection against deleterious mutations. Theoretical advances have provided important insights into the extent to which demographic history influences selection strengths and genetic load. There is growing recognition that nonequilibrium demographic history can lead to spurious signals of increased genetic load. Model-based methods investigating the efficacy of selection, incorporating demographic history and uncertainty in the dominance of deleterious mutations, are being developed to provide further insights into the factors limiting selection in natural populations.